Genotyping for human papillomavirus (HPV) 16/18/52/58 has a higher performance than HPV16/18 genotyping in triaging women with positive high-risk HPV test in Northern Thailand - Khunamornpong S. (2017)
© 2016 Khunamornpong et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background Testing for high-risk human papillomavirus DNA (HPV test) has gained increasing acceptance as an alternative method to cytology in cervical cancer screening. Compared to cytology, HPV test has a higher sensitivity for the detection of histologic high-grade squamous intraepithelial lesion or worse (HSIL+), but this could lead to a large colposcopy burden. Genotyping for HPV16/18 has been recommended in triaging HPV-positive women. This study was aimed to evaluate the screening performance of HPV testing and the role of genotyping triage in Northern Thailand. Methods A population-based cervical screening program was performed in Chiang Mai (Northern Thailand) using cytology (conventional Pap test) and HPV test (Hybrid Capture 2). Women who had abnormal cytology or were HPV-positive were referred for colposcopy. Cervical samples from these women were genotyped using the Linear Array assay. Results Of 5,456 women, 2.0% had abnormal Pap test results and 6.5% tested positive with Hybrid Capture 2. Of 5,433 women eligible for analysis, 355 with any positive test had histologic confirmation and 57 of these had histologic HSIL+. The sensitivity for histologic HSIL+ detection was 64.9% for Pap test and 100% for Hybrid Capture 2, but the ratio of colposcopy per detection of each HSIL+ was more than two-fold higher with Hybrid Capture 2 than Pap test (5.9 versus 2.8). Genotyping results were available in 316 samples. HPV52, HPV16, and HPV58 were the three most common genotypes among women with histologic HSIL+. Performance of genotyping triage using HPV16/18/52/58 was superior to that of HPV16/18, with a higher sensitivity (85.7% versus 28.6%) and negative predictive value (94.2% versus 83.9%). Conclusions In Northern Thailand, HPV testing with genotyping triage shows better screening performance than cervical cytology alone. In this region, the addition of genotyping for HPV52/58 to HPV16/18 is deemed necessary in triaging women with positive HPV test.